2010
DOI: 10.1007/s10734-010-9381-z
|View full text |Cite
|
Sign up to set email alerts
|

Inclusiveness in higher education in Egypt

Abstract: In Egypt, before 1952, education, especially higher education, was the province of a privileged few. After the 1952 Revolution, in pursuit of social justice and economic development, Egypt's leaders eliminated fees, instituted a universal admission examination, promised government employment to all graduates of higher education, and expanded the number of places. Officials expected these policies to increase inclusiveness as enrollments grew. We examine the period from 1988 through 2005, when egalitarian polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…While historically, the Egyptian Government initiated equality, diversity and inclusivity policies, unfortunately this was not a prioritized practice across the sector. In a study in inclusiveness in higher education in Egypt, Cupito and Langsten [17] found that since 1952 Revolution, in pursuit of social justice and economic development, Egypt's leaders eliminated fees, instituted a universal admission examination, promised government employment to all graduates of higher education, and expanded the number of places, and officials expected these policies to increase inclusiveness as enrollments grew, however inclusiveness did not change for males and, at best, modestly improved for females, and that young adults from the wealthiest families maintained a substantial advantage in the likelihood of enrolling in higher education.…”
Section: Participating Universities and Personnelmentioning
confidence: 99%
“…While historically, the Egyptian Government initiated equality, diversity and inclusivity policies, unfortunately this was not a prioritized practice across the sector. In a study in inclusiveness in higher education in Egypt, Cupito and Langsten [17] found that since 1952 Revolution, in pursuit of social justice and economic development, Egypt's leaders eliminated fees, instituted a universal admission examination, promised government employment to all graduates of higher education, and expanded the number of places, and officials expected these policies to increase inclusiveness as enrollments grew, however inclusiveness did not change for males and, at best, modestly improved for females, and that young adults from the wealthiest families maintained a substantial advantage in the likelihood of enrolling in higher education.…”
Section: Participating Universities and Personnelmentioning
confidence: 99%
“…Tracking in secondary school is a key determinant of access to higher education (Cupito and Langsten 2011;Langsten 2015). At the time of the 1952 revolution, almost all secondary students (around 95%) were enrolled in the general (academic) secondary track (Richards 1992;Szyliowicz 1973).…”
Section: Access To Egyptian Higher Educationmentioning
confidence: 99%
“…Aged between 15 and 35 years old, they sweep through all social classes of society, though a large portion of their members belong to the upper classes of Egyptian society, unlike their European counterparts (Hourcade 2000;El-Zatmah 2012;Lebrun 2013). 18 What is more, many Ultras -regardless of social class -are well educated and carry a University degree or are currently pursuing studies, as a result of the free education system for public schools in Egypt, the private system being more expensive (Cupito;Langsten 2011). 19 So the main issue for these young Egyptians resides in the imposed set of goals to achieve and norms to respect according to their social status and qualifications.…”
Section: From Stadium To Street: the Ultras' Mobilization Processesmentioning
confidence: 99%
“…19. Regarding the public and private education system in Egypt, seeHyde 1978; Arum; Gamoran; Shavit 2007;Cupito; Langsten 2011. 20.…”
mentioning
confidence: 99%